Pengaruh Penambahan Kalium Sorbat terhadap Mutu Daging Kebab Iris - Farha Herzegovina; Sugiyono Sugiyono; Nugraha Edhi Suyatma (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Sliced kebab meat is produced by roasting raw kebab meat to make it easier to distribute at cold temperature. However, its quality could be damaged if it is distributed for long period, so preservative is needed. The study consisted of two phases. The first phase determined the type and concentration of preservatives consisting of potassium sorbate at concentrations of 750, 1000, 1250 ppm, and sodium nitrite at concentrations of 30, 50, and 100 ppm used a completely randomized design. The second phase was carried out to study the stability of sliced kebab meat with the addition of selected preservatives during refrigeration storage (5°C). The results showed that the best treatment was the use of potassium sorbate at 1250 ppm which resulted in the lowest mean total plate count (TPC), mold yeast values, and the highest scores of sensory attributes. The stability could be maintained at refrigeration storage for up to 14 days. On the 14th day, the sliced kebab meat had a pH value of 6.59, aw of 0.70, total acidity of 0.55%, TPC of 2.81 logs CFU/g, the color score of 3.8 (slightly brownish red), the aroma of 4 (typical meaty smell), the taste of 3.8 (slightly the savory), the texture of 3.5 (neutral) and overall of 3.5 (rate as liked).